2017
DOI: 10.7759/cureus.1012
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Stereotactic Insertion of Viewsite Brain Access System with Microscope-Mounted Tracking Device for Resection of Deep Brain Lesions: Technical Report

Abstract: The surgical management of deep brain tumors is often challenging due to the limitations of stereotactic needle biopsies and the morbidity associated with transcortical approaches. We present a novel microscopic navigational technique utilizing the Viewsite Brain Access System (VBAS) (Vycor Medical, Boca Raton, FL, USA) for resection of a deep parietal periventricular high-grade glioma as well as another glioma and a cavernoma with no related morbidity. The approach utilized a navigational tracker mounted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…White et al. 397 developed a microscopic navigation system combined with the Viewsite Brain Access System (VBAS) technique for deep brain lesions and employed this system in high-grade glioma surgery. After craniotomy, the microscope with the navigation system was registered to the position and placed over the exposed surgical site.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…White et al. 397 developed a microscopic navigation system combined with the Viewsite Brain Access System (VBAS) technique for deep brain lesions and employed this system in high-grade glioma surgery. After craniotomy, the microscope with the navigation system was registered to the position and placed over the exposed surgical site.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…10,11,27 To combat these effects when tackling deep-seated intracranial lesions, several iterations of fiber-sparing tubular retractor systems have been developed to provide safe surgical corridors for accessing and resecting deep-seated lesions. 15,17,[28][29][30][31] In addition, visualization is difficult because adequate light is needed to reach the tumor. 12 Exoscopes help provide adequate lighting, greater degree of freedom, larger focal point ranges, and more maneuverability than typical surgical microscopes.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently described lesion was glioma. [10][11][12][13][14][15] The ViewSite Brain Access System is a completely transparent assembly (including the introducer) allowing for continuous monitoring of the dissection corridor. 10 Whereas some authors described the need to "dissect a few centimeters of white matter to accommodate the retractor," 11,13 Recinos et al argued that the "elliptical shape of the retractor split the deep matter thus negating the need for white matter resection."…”
Section: Viewsite Brain Access Systemmentioning
confidence: 99%
“…All the authors agreed that the use of tubular retractors, especially in the resection of deep-seated lesions, was a safe and effective surgical approach. [10][11][12][13][14][15] Herrera et al observed that the even force distributed across retracted brain tissues when using ViewSite Brain Access System reduced the rate of retraction-related complications. 10 This observation was supported by Recinos et al, who felt that the use of tubular retractors was advantageous in pediatric populations to curtail the risk of long-term sequelae associated with white matter damage.…”
Section: Viewsite Brain Access Systemmentioning
confidence: 99%